Enhancing Social-Emotional Skills through Traditional Bakiak Games in Group B Children at KB. Raudhatul Jannah - Delpiyani, Delpiyani; Anugrah, Yuwan Fijar; Sari, Nadia Tiara Antik; Rajasa, Gilang (Kiddie: Early Childhood Education and Care Journal, 2025)
Social emotional abilities are one of the supporters of multiple intelligence. This skill is absolutely necessary for every individual to face the surrounding community. So it is better if this ability is trained from an early age. aspects of emotional side development, because this aspect has a fairly large role in the child's life in the future. Therefore, this research aims to improve social emotional skills in young children through playing the traditional game of clogs originating from West Sumatra. This research is classroom action research (PTK) which was carried out in 2 cycles, including the planning stage, action stage, observation stage and also reflection. The aim of this research is to determine whether there is an increase in the social emotional abilities of young children through clog playing activities in group B at KB Raudhatul Jannah, Jatiluhur subdistrict, Purwakarta district. The research subjects were 20 children consisting of 6 girls and 14 boys. The data collection techniques used are observation and documentation. Results from observing the social emotional abilities of group B children in KB. Raudhatul Jannah after quantitative and qualitative descriptive analysis. Achievement target or maximum value is 75%-100%. In the pre-cycle or before the action, the social emotional skills achievement value was 39,5%. Implementation of cycle I increased to 54%. Then in cycle II it became 89%. This means that using the traditional clog game playing method can improve the social emotional abilities of group B children in KB. Raudhtul Jannah.